Reply to Emv2, the only endogenous ecotropic murine leukemia virus of C57BL/6J mice - Lee, Kang-Hoon (BioMed Central, 2012)
This correspondence was written in response to the comments by Young et al. Following careful evaluation of the relevant dataset, each of the points brought up by Young et al. has been addressed in this response. We anticipate this will clarify our findings regarding ERV(mch8), an ecotropic endogenous retrovirus that was shown to have cerebellum-specific and age-dependent expression patterns in C57BL/6J mice.